Synergy between Vancomycin and Nafcillin against Staphylococcus aureus in an In Vitro Pharmacokinetic/Pharmacodynamic Model - Leonard, Steven N. (PLOS ONE, 2012)
Introduction Continued pressure from glycopeptide use has led to non-susceptible strains of Staphylococcus aureus including heterogeneously vancomycin-intermediate S. aureus (hVISA). Infections with hVISA are associated with poor patient outcomes, thus incentivizing novel treatments. Evidence suggests that vancomycin and anti-staphylococcal penicillin susceptibility are inversely related which indicates that the use of this combination may be particularly useful against methicillin-resistant S. aureus with reduced susceptibility to vancomycin, such as hVISA. The aim of this study was to evaluate the potential for synergy between vancomycin and nafcillin against hVISA. Methods Twenty-five hVISA strains were evaluated for vancomycin and nafcillin minimum inhibitory concentration (MIC) by broth microdilution in duplicate. Potential for synergy was assessed by time-kill at 1/2x MIC in triplicate. Five strains were chosen, representing the range nafcillin MIC’s available in the cohort –4, 16, 64, 128, and 256 µg/mL, and were run in an in vitro pharmacokinetic/pharmacodynamic (PK/PD) model in duplicate over 72 hours to evaluate the potential of the combination with simulated human pharmacokinetics. In addition, 4 fully glycopeptide susceptible strains of S. aureus including 2 methicillin-susceptible (MSSA) and 2 methicillin-resistant (MRSA) were run in the PK/PD model for comparison. Results In the time-kill, 92% of strains (23 of 25) displayed synergy with the combination of vancomycin and nafcillin. In the PK/PD model, all five strains of hVISA showed an improvement in overall activity (P≤0.004) and organism burden at 72 hours (P≤0.001) with the combination compared to either drug alone. The combination was also successful against both MRSA and MSSA in overall activity (P≤0.009) and organism burden at 72 hours (P≤0.016), though the magnitude of the effect was diminished against MSSA. Conclusions The combination of vancomycin and nafcillin significantly improved antibacterial activity against hVISA, MRSA, and MSSA compared to either drug alone.